Realistic mathematics education combined with guided discovery for improving middle school students’ statistical literacy - Titi Adriani Hakim; Wahyu Setyaningrum (Journal of Honai Math)
Statistical literacy is essential for students to evaluate and mitigate the spread of biased information critically and to make well-informed decisions grounded in data. Despite its recognized significance, many students face challenges in grasping statistical concepts. While Realistic Mathematics Education (RME) has demonstrated efficacy in enhancing overall mathematics learning outcomes, its specific influence on statistical literacy remains underexplored. This study sought to evaluate the effectiveness of integrating RME with guided discovery and Quizizz to enhance statistical literacy among middle school students. This approach utilized real-world contexts, facilitated active exploration, and provided personalized feedback to foster deeper understanding and engagement. Employing a pre-experimental design, the study involved 26 eighth-grade students and utilized a one-group pretest-posttest framework. The results indicated that post-test scores met the established passing criteria, with over 85% of students achieving classical completeness in learning. These results highlight the effectiveness of combining RME with guided discovery and Quizizz in advancing statistical literacy among middle school students. This research offers valuable insights into effective instructional strategies for promoting statistical literacy and provides practical implications for educators and curriculum developers aiming to innovate educational practices.